2009
DOI: 10.1111/j.1467-9787.2008.00593.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the Ghosh Model Interesting?*

Abstract: The overall value of the Ghosh model is appraised. Its treatment of quantities and prices is scrutinized by examining the variant with data in quantities and prices, and the variant with data in value and price indexes. The methodology involves returning to the accounting equations and shows that: (i) the Ghosh model offers solutions of limited interest, being incapable of providing prices or price indexes separately from quantities; (ii) what is taken to be the equation of Ghosh's value model is actually that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 19 publications
1
25
0
1
Order By: Relevance
“…The Ghosh model has been criticized by researchers such as Dietzenbacher (); however, the criticism is directed toward the causal interpretation of resource consumption in a sector based on resource entering in other sectors. If the causal interpretation is not the intent, as is the case in this work, then such criticisms of the Ghosh model should be ignored (Miller and Temurshoev ; de Mesnard ).…”
Section: Approachmentioning
confidence: 90%
“…The Ghosh model has been criticized by researchers such as Dietzenbacher (); however, the criticism is directed toward the causal interpretation of resource consumption in a sector based on resource entering in other sectors. If the causal interpretation is not the intent, as is the case in this work, then such criticisms of the Ghosh model should be ignored (Miller and Temurshoev ; de Mesnard ).…”
Section: Approachmentioning
confidence: 90%
“…159 and following;2009 pp. 230 and following) but it is compatible with Eurostat's equation (Eurostat 2008, pp.…”
Section: Remind: Derivation Of Symmetric Io Tables With the Four Modelsmentioning
confidence: 99%
“…ten Ra (1988) has understood that negative terms are not due to errors in the data but to the model. The present author (de Mesnard 2004) has shown that, if the model is interpreted in terms of circuit, it cannot be demand-driven as usual and the product-technology assumption corresponds to the so-called supply-driven Ghosh model, largely criticized (Dietzenbacher 1997;de Mesnard 2009). where x i is the output of industry i (x i > 0 for any i), w j the value added of industry j (w j > 0 for any j), q i the total production of product i (q i > 0 for any i) and e i is the amount of product i sold to final demand (e i > 0 for any i).…”
Section: Remind: Derivation Of Symmetric Io Tables With the Four Modelsmentioning
confidence: 99%
“…Questions on the plausibility of the Ghosh model were first proposed by Oosterhaven (1988) who concluded the supply-driven model was "theoretically implausible" and deterred its use for studying markets that were typically not facing supply constraints. Although the most fervent opposition to the Ghosh model came from Oosterhaven (1988;1989;2012) many authors continue to utilise and advocate the use of the Ghosh model for different specialist purposes (Dietzenbacher 1997;Dietzenbacher and Hoen 2006;De Mesnard 2007;De Mesnard 2009;Guerra and Sancho 2011). As already noted, the Ghosh model has proven particularly useful for estimating the impacts of supplyconstrained economies, centrally planned economies or economies with monopolistic behaviour.…”
Section: The Supply Side Input-output Ghosh Modelmentioning
confidence: 99%